Single-needle arthrocentesis with upper compartment distension versus conventional two-needle arthrocentesis : randomized clinical trial - Grossmann, Eduardo (2017)
The objective of this study was to compare single-needle arthrocentesis with distension of the upper compartment of the temporomandibular joint (TMJ) with the conventional two-needle arthrocentesis. Twenty-six patients with articular disc displacement without reduction (DDWOR) were included in the study and assigned to two groups ( = 13): single-needle arthrocentesis with distension of the upper compartment of the TMJ (1N) and conventional two-needle arthrocentesis (2N). The maximum interincisal distance (MID) and TMJ pain as measured by the visual analog scale (VAS) were compared. MID and VAS data were obtained: before (T1), seven days after (T2), fifteen days after (T3), one month after (T4), three months after (T5), six months after (T6), nine months after (T7), and one year after the arthrocentesis procedures (T8). Considering each group individually, results of the VAS scores and MID measurements showed a significant difference between T1 and T2–T8 ( < 0.001) in both groups. Between two groups, results show no significant differences ( > 0.05). Both techniques tested were effective in reducing pain and increasing MID. Due to the advantages over the conventional two-needle arthrocentesis, single-needle arthrocentesiswith distension of the upper compartment should be considered as the first treatment option for patients with painful hypomobilized TMJ of DDWOR.